Pemberdayaan Gapoktan Sepakat Melalui Penguatan Lembaga Pemasaran Sayur Sehat Bersertifikat Prima Di Nagari Canduang Koto Laweh, Sumatera Barat - Melinda Noer; Herviyanti Herviyanti; Cesar Welya Refdi; An NIsa Mutiara Fathi (LPPM Universitas Andalas, 2025)
Empowering the Sepakat Farmers Group Association (Gapoktan) aims to strengthen the capabilities of Gapoktan, who cultivate Prima-certified vegetable horticulture, but has not been able to develop its agribusinesses that give an impact on economic improvement to its members. Since 2021, several types of vegetables produced by Gapoktan have been receiving certification from the West Sumatra Provincial Food Service as a guarantee that pesticide levels in these vegetables are below the threshold, making them safe for consumption. However, Gapoktan still faces obstacles in marketing, because the market does not differentiate the price of certified and uncertified vegetables. The activity methods include outreach, practices for processing inputs based on local resources, and processing healthy vegetable products into snacks to add value and durability, as well as strengthening marketing institutions for Prima-certified products. Gapoktan has been linked with the Canduang Koto Laweh State-Owned Enterprise as a marketing partner for Prima-certified vegetables, opening new marketing relationships to intermediate consumers, such as hospitals. The Agam Regency Government will also revitalize the Agribusiness Sub-Terminal (STA) and the Agribusiness Micro-Credit Institution (LKMA) to receive Prima-certified vegetable products at more reasonable prices. In the short term, this empowerment program for farmer groups (Gapoktan) has resolved marketing barriers, increased product added value, and expanded access to agricultural markets. It is hoped that in the long term, through strengthened marketing institutions, Prima-certified vegetable products will be more competitive and their market share will expand, thereby further increasing farmer interest and welfare in developing Prima-based healthy vegetable farming.